2018
DOI: 10.1108/ijbpa-01-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of mass housing: size modification of flats as a response to segregation

Abstract: When dwellings fail to respond to residents' needs, housing will suffer from segregation and buildings will possibly be demolished ahead of their time. This paper focuses on the lack of variation in the sizes of dwellings as a factor in residential segregation. It examines this issue in the context of Finnish mass housing built in the 1960s and 1970s. The aim of the article is to review how mass housing layouts can be adapted to produce the currently absent flat sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Categorising the values explored in every study, similar patterns have been found for stage 1 (230 articles) and stage 2 (45 articles). Figure 2(a) illustrates the 1:3 ratio between the number of studies that focus on one specific type of value and studies that explore more (Huuhka, 2018;Song, 2012;Adair, 2014;Asan, 2018). The functionality of residential areas as a research topic is not limited to the financial-economic discipline, explaining the large share of research studies focussing on economic values.…”
Section: Type Of Valuesmentioning
confidence: 99%
“…Categorising the values explored in every study, similar patterns have been found for stage 1 (230 articles) and stage 2 (45 articles). Figure 2(a) illustrates the 1:3 ratio between the number of studies that focus on one specific type of value and studies that explore more (Huuhka, 2018;Song, 2012;Adair, 2014;Asan, 2018). The functionality of residential areas as a research topic is not limited to the financial-economic discipline, explaining the large share of research studies focussing on economic values.…”
Section: Type Of Valuesmentioning
confidence: 99%
“…In addition to the advantage that smaller size rooms may offer, providing rooms, which like the guestroom in the CRH flat, allow for independent use of sanitary conveniences, become even more useful. The possibilities for apartment sharing draws attention to the fact that proper space planning and layout based on carefully considered variations in the number and sizes of rooms, relationship between rooms, slightly generous usable floor area, and little overt expression of room functions are critical to the long-term usability and adaptability of dwelling units that lead of increased satisfaction (Huuhka and Saarimaa, 2018). Table II shows that the case studies used have these built-in features.…”
Section: Residential Adaptations Through Manipulation Of Built-in Design Capacitymentioning
confidence: 99%
“…It is anticipated that the majority of existing buildings will be frequently adapted in the upcoming decades to meet future demands (Bullen, 2007;Conejos et al, 2014;Perolini, 2013;Rasmussen, 2012). Consequently, it is argued that adaptability should be proactively and reactively incorporated, meaning that existing and new buildings should facilitate the accommodation of future changes (Huuhka, and Saarimaa, 2018;Langston, 2014a).…”
Section: Introductionmentioning
confidence: 99%